Exploring Literacies Theory, Research and Practice - de Silva Joyce, Helen; Feez, Susan (Research and Practice in Applied Linguistics, 2016)
This book is a guide to current research and debate in the field of literacies practice and education. It provides both an historical and lifespan view of the field as well as an overview of research methodologies with first-hand examples from a range of researchers involved in literacy research.